Platycodon grandiflorum exhibits anti-neuroinflammatory potential against beta-amyloid-induced toxicity in microglia cells - Ji, Yun-Jeong; Kang, Min Hye; Kim, Geum-Soog; Kim, Hyung Don; Jang, Gwi Yeong (Frontiers in Nutrition, 2024)
Background/objectives: Platycodon grandiflorum (PG) is used in traditional oriental medicine to treat several ailments. Methods: The study investigated the anti-inflammatory and neuroprotective effects of PGW (P. grandiflorum) extract in Aβ25-35-induced inflammation in BV2 microglia cells. Result: PGW demonstrated significant inhibition of nitric oxide (NO) production, with reductions of 30.4%, 36.7%, and 61.2% at concentrations of 50, 100, and 200 μg/mL, respectively. Moreover, PGW effectively suppressed the production of pro-inflammatory cytokines IL-1β and IL-6 and exhibited significant inhibitory activity against TNF-α at 200 μg/mL. Furthermore, PGW treatment mitigated apoptosis in Aβ-induced BV2 cells by modulating the mitochondrial apoptosis pathway, regulating Bcl-2 family protein synthesis, and inhibiting caspase activation. Mechanistically, PGW attenuated the activation of the MAPK (JNK, ERK, p38) pathway induced by Aβ, showing a concentration-dependent decrease in phosphorylation levels of these proteins. Additionally, PGW inhibited the NF-κB pathway activation by reducing the phosphorylation levels of p65 and IκBα in a concentration-dependent manner. Conclusion: PGW demonstrated anti-inflammatory and neuroprotective effects in Aβinduced neuronal cells, suggesting its potential as a therapeutic agent for neuroinflammatory associated with neurodegenerative diseases.